Cause and Effect of using Digital Content in Biology Subject at Grade IX-X in Dhaka City (Global Journal of Human-Social Science, 2017)
Information and communication technologies ICT have become everyday entities in all spheres of life ICT has fundamentally changed the pedagogy in education lend itself to more student-centred learning phenomena hereafter digital content an ubiquitous part of ICT is becoming more and more important The purpose of the present paper is to examine the relationship between the use of digital content and students performance and to give complementary explanations regarding causes and effects of using digital content in secondary education especially in biology subject This study followed mixed method design including qualitative and quantitative data The result of the study revealed that student s performance is mainly explained by student s characteristics educational environment and teachers characteristics and digital content have a concrete impact on these determining factors and consequently the outcome of education The adoption of ICT equipment and use rates is relatively slow and differs from one institution to another Henceforth use of computer supportive instructional material need a change in the organisation of secondary education Government or PPP or school authority can take benign initiative to provide low-cost laptop multimedia projector Furthermore continuous in-servicing training should be provided among teachers to ensure digitalized classroom and effective teaching-learning process
Keywords: digital content; cause; effect; biology subject; secondary level of education; mixed method